Peran Media YouTube Masjid Al-Irsyad Surabaya sebagai Strategi Komunikasi Dakwah di Era Digital - Johari Muis (PROGRESIF: Jurnal Dakwah, Sosial, dan Komunikasi, 2025)
The rapid development of digital technology has significantly transformed the pattern of Islamic da’wah communication. However, limited research has explored how religious institutions such as mosques utilize digital platforms strategically for da’wah. This study aims to analyze the role of the YouTube channel of Al-Irsyad Mosque Surabaya in developing da’wah communication strategies in the digital era. This research employs a qualitative descriptive method with a case study approach, using video content observation, interviews with channel administrators, and documentation of the mosque’s digital activities. The findings indicate that the YouTube channel of Al-Irsyad Mosque serves four primary da’wah functions: informative, educative, persuasive, and recreational. The communication strategies implemented include attractive visual presentation, selection of relevant da’wah themes, involvement of young preachers, and consistent content uploading. By utilizing YouTube, Al-Irsyad Mosque is able to expand its da’wah outreach globally and develop an adaptive model of da’wah communication in response to technological change. These findings emphasize that YouTube is not merely a publication platform, but a strategic instrument for mosque-based da’wah in the digital era.